Phytoliths – A tool for paleoenvironmental reconstitution studies : Concepts and review on applications in Brazil - Calegari, Marcia Regina (2022)
Phytoliths are microscopic structures of hydrated silica (SiO2.nH2O) produced in plant tissues. The interest in studying phytoliths has grown significantly in recent years in Brazil and worldwide due to their wide variety of uses, from archaeology to forensic sciences, and their highly interdisciplinary nature. Phytolith analysis has recently been understood as a superdiscipline, which pervades different leves of analysis. Studies on phytolith production, shape and size diversity, and analysis/interpretation of assemblages preserved in soils and sediments have contributed to understanding paleoenvironmental and paleoarchaeobotanical questions. Considering the relevance and visibility that phytolith analysis has presented, especially in Brazil, a review of the main aspects related to this technique and its applications in Brazil is presented in this study.